Development of the plant collection prescription and the obtaining a liquid extract technology on its basis for prevention and treatment of musculoskeletal system diseases - О. P. Khvorost; T. V. Oproshanska; K. S. Skrebtsova; O. S. Shpychak; A. M. Solomennyi; О. О. Davydenko; О. V. Golyuk (Український журнал військової медицини)
Purpose. Development of the composition of the plant collection “Opornofit” and the technology of obtaining a liquid extract on its basis for the prevention and treatment of diseases of the musculoskeletal system, with the determination of quality indicators and stability during their storage.